Application of the Giving Question and Getting Answer Method to Improve Student Learning Outcomes in Islamic Religious Education Class VIII H MTs Wali Songo Ngabar Ponorogo - Muhammad Yusron Fahmi; Riky Syaputra; Imam Rohani (Tarbawi: Journal of Islamic Education, 2022)
This classroom action research aims to improve the quality of student learning outcomes in Islamic Religious Education subjects. The alternative offered to achieve that goal is to introduce the method of giving questions and getting answers. This research uses Kurt Lewin's Class Action Research (CAR) method. Data collection techniques used are observation and tests. Classroom Action Research in class VIII H MTs Wali Songo Ngabar. The steps of data analysis are as follows: data selection, data correction and data weighting. The results of this study prove that the giving question and getting answer method has succeeded in improving the quality of student learning outcomes in Islamic Religious Education subjects in class VIII H MTs Wali Songo Ngabar.